2016
DOI: 10.1051/0004-6361/201628550
|View full text |Cite
|
Sign up to set email alerts
|

Measuring turbulence in TW Hydrae with ALMA: methods and limitations

Abstract: Aims. We aim to obtain a spatially resolved measurement of velocity dispersions in the disk of TW Hya. Methods. We obtained images with high spatial and spectral resolution of the CO J = 2-1, CN N = 2-1 and CS J = 5-4 emission with ALMA in Cycle 2. The radial distribution of the turbulent broadening was derived with two direct methods and one modelling approach. The first method requires a single transition and derives T ex directly from the line profile, yielding a v turb . The second method assumes that two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
227
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(260 citation statements)
references
References 25 publications
33
227
0
Order By: Relevance
“…By carefully investigating for CO, CN and CS observations of the disk system TW Hya, Teague et al (2016) found an upper limit of the turbulence causing line broadening, consistent with v turb ≤ 0.2c s . Another ALMA observation of the disk HD 163296 in different CO lines by Flaherty et al (2015) supports the general finding of relatively low turbulent velocities in the disk.…”
Section: Kinematic Constraints From Line Observationsmentioning
confidence: 72%
“…By carefully investigating for CO, CN and CS observations of the disk system TW Hya, Teague et al (2016) found an upper limit of the turbulence causing line broadening, consistent with v turb ≤ 0.2c s . Another ALMA observation of the disk HD 163296 in different CO lines by Flaherty et al (2015) supports the general finding of relatively low turbulent velocities in the disk.…”
Section: Kinematic Constraints From Line Observationsmentioning
confidence: 72%
“…Within this radius the continuum emission dominates the weaker CS emission, thus continuum subtrac- tion may affect the assumed inner radii of CS. Outside of this, the emission falls off and is detected to ∼ 3.7 (Teague et al 2016), comparable to that of CO and scattered light (Andrews et al 2012;Debes et al 2013). …”
Section: Radial Featuresmentioning
confidence: 88%
“…The change in density structure and Elsasser number over this boundary forms axisymmetric zonal flows, carving the gap. A measurement of the radial extent of the dead-zone (or confirmation of its presence) would provide a great test for this instability, however previous analyses of the ionization and turbulent velocity structures have yet to detect the edge (Cleeves et al 2015b;Teague et al 2016). Furthermore, Flock et al (2015) note that no structure is seen in simulated scattered light images, contrary to the case for TW Hya.…”
Section: Disk Instabilitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In that case the midplane-relevant here-stays laminar. Given these uncertaintiesindeed˛T is very hard to constrain observationally (Teague et al 2016)-it is best to consider˛T as a free parameter and test how it affects the pebble accretion rates.…”
Section: The Pebble Accretion Growth Mass M P;grwmentioning
confidence: 99%